2022
DOI: 10.3389/fimmu.2022.833085
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response Diversity to Different COVID-19 Vaccines: Implications for the “Green Pass” Policy

Abstract: In the COVID-19 pandemic year 2021, several countries have implemented a vaccine certificate policy, the “Green Pass Policy” (GPP), to reduce virus spread and to allow safe relaxation of COVID-19 restrictions and reopening of social and economic activities. The rationale for the GPP is based on the assumption that vaccinated people should maintain a certain degree of immunity to SARS-CoV-2. Here we describe and compare, for the first time, the humoral immune response to mRNA-1273, BNT162b2, Ad26.COV2.S, and Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…The diversity of immune responses to SARS-CoV-2 strains during viral infection is associated with multiple factors such as structural and non-structural viral proteins, genetic diversity of MHC Class I and II genes in the population, immune robustness, and co-morbidities of infected individuals 13 , 14 . In healthy individuals, these responses culminate into responses attributed to a mix of CD8 cytotoxic T cells, CD4 effector T cells, and antibody-secreting B cells.…”
Section: Diversity Of Immune Responses and Long-term Immune Memorymentioning
confidence: 99%
“…The diversity of immune responses to SARS-CoV-2 strains during viral infection is associated with multiple factors such as structural and non-structural viral proteins, genetic diversity of MHC Class I and II genes in the population, immune robustness, and co-morbidities of infected individuals 13 , 14 . In healthy individuals, these responses culminate into responses attributed to a mix of CD8 cytotoxic T cells, CD4 effector T cells, and antibody-secreting B cells.…”
Section: Diversity Of Immune Responses and Long-term Immune Memorymentioning
confidence: 99%
“…The available vaccines induce SARS-CoV-2-specific cellular and antibody responses but a major goal is to induce virus-neutralizing antibodies against the S protein and in particular against the RBD of SARS-CoV-2 [ 28 , 29 ]. Similarly to what is observed after natural infection, it was found that COVID-19 vaccines induce a heterogeneous S-specific antibody response regarding antibody titers and virus neutralizing capacity [ 15 , 30 , 31 ]. Importantly, neutralizing antibodies induced by infection as well as by vaccination were found to decrease after a few months [ 32 , 33 , 34 , 35 ], and accordingly breakthrough infections were noted even after booster vaccinations [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 80%
“…No clear cause could be identified, as patients had no relevant comorbidities or comedication, no lymphopenia and both received two vaccination doses. The seronegative patients were somewhat older (53 and 56), which could be a contributing factor since higher age has been associated with a higher probability of low- or non-response to vaccination [21] , [22] . However, the present study finds a similar seropositivity rate as found in studies in large samples from the general population [23] .…”
Section: Discussionmentioning
confidence: 99%